Kajian Literatur Pengasuhan Anak Usia Dini Dalam Islam - Imroatun Imroatun; Ine Nirmala; Juhri Juhri; Birru Muqdamien (UIN Sultan Maulana Hasanudin Banten, 2020)
This literature research aims to add insight for parents of dual careers in caring for children independently or empowering other parties. All the considerations in it must refer to the Quran and Hadith. Including efforts to achieve the ideal parenting style. Parenting provided by parents to children has a variety of models and patterns between one family and another family. The main factors that influence in the form of changes in the position and relationship of parents and families with children.